THE MEDIATING ROLE OF AUDIT QUALITY IN THE RELATIONSHIP BETWEEN NON-FINANCIAL FACTORS OF AUDIT FEES - Hidayat, Imam; Abbas, Dirvi; Hamdani, Hamdani; Saad, Asni (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2024)
The Sun Nusantara Prima (SNP) designed incorrect receivables by generating fictitious sales with Columbia client data. It was unfortunate that Deloitte, the auditor, was unable to report the detection of a fraudulent scheme in SNP's financial statements. The research aims at investigating the influence of firm complexity, size, and independent commissioners on audit fees. The research's population consisted of manufacturing companies that were listed on the BEI. The complexity of the firm and Audit quality influenced the audit fee. Company size and The Independent Commissioner had no significant effect on audit fees. Furthermore, the Company's Complexity affected audit costs with audit quality as a mediating variable. These findings were inconsistent with the agency's theory, where lack of independent commissioner supervision suppressed management intervention against auditors so that sometimes they were given information that was not relevant and reliable. Therefore, public accountants made mistakes in making their opinions.